Pengaruh Jarak Rumah Siswa Dengan Sekolah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas 7 SMP Negeri 2 Gunungsitoli Alo’oa - Fitri Arni Zebua; Delvi Wardani Telaumbanua; Agnes Renostini Harefa (Peneliti.net, 2023)
Residence is the presence of students or the presence of student houses. So the residence referred to in this study is the house occupied by students every day. Student learning outcomes can be influenced by internal factors and external factors of students. Internal factors of students include the level of intelligence, emotion, interest, psychology and talent. External factors include the educational level of parents, economic class, distance from home, teachers, teaching materials, learning environment and association. In accordance with the title of the journal, to find out about the absence of an effect of distance between residence and student learning outcomes, it is necessary to conduct research with the aim of providing input for publishers, especially junior high school level teachers. This study aims to determine the effect of the distance traveled by students to school on student achievement at school and to determine the relationship between the distance traveled by students to school on student achievement. This research is qualitative, the research instrument used is in the form of interview text in the form of fields, and also distributes essay tests to see student learning outcomes. In the research that has been done, there are locations where the house to school is too far away, 5 km away, and there is a short distance of 1 km. In accordance with the student data that has been contained in the table, it can be seen that the distance between the student's house and the school is one of the factors that influence student academic achievement.